Sexual violence during the war: towards an understanding of variation (2009)
This article focuses on sexual violence against civilians by the combatants. First, it resumes the variation patterns of violence form and extension throughout the different wartime situations. In particular, the absence of sexual violence in some conflicts and by some armed groups is here with documented. After discussing the methodological challenges to compile and analyze the information on sexual violence, it is argued that the topic deserves an extended comparative analysis since there is an ample enough variation across really well documented cases. An evaluation is made about whether the causal mechanisms identified in the literature (often implicit) explain the variation. In the conclusion, an analytical framework scheme is made for the study of sexual violence as part of the violence repertoires of the armed groups and also a suggestion is made about several research designs which can contribute to the academic understanding of sexual violence and other forms of violence.